Design of a system for controlling a levitating sphere in superfluid 3He at extremely low temperatures - Manuel Arrayás (Nature Portfolio, 2021)
Abstract We present a new mechanical probe to study the properties of superfluid 3He at microkelvin temperatures down to 100 μK. The setup consists of a set of coils for levitating a superconducting sphere and controlling its motion in a wide variety of regimes. In particular, the realisation of motion of a levitating body at a uniform velocity presents both an experimental challenge and a promising direction into the study of the edge states in topological superfluid 3He-B. We include the theoretical study of the device stability and simulations to illustrate the capabilities of the control system.